Use of Intron-Disrupted Polyadenylation Sites To Enhance Expression and Safety of Retroviral Vectors - Ismail, Said I. (American Society for Microbiology, 2001)
Normal mRNA polyadenylation signals are composed of an AAUAAA motif and G/U box spaced 20 to 30 bp apart. If this spacing is increased further, then polyadenylation is disrupted. Previously it has been demonstrated that insertion of an intron will similarly disrupt this signal even though such introns are removed during a nuclear splicing reaction (X. Liu and J. Mertz, Nucleic Acids Res. 21:5256–5263, 1993). This observation has led to the suggestion that polyadenylation site selection is undertaken prior to intron excision. We now present results that both support and extend these observations and in doing so create a novel class of retroviral expression vector with improved qualities. We found that when an intron-disrupted polyadenylation signal is inserted within a retroviral expression vector, such a signal, although reformed in the producer cell, remains benign until transduction, where it is then preferentially used. Thus, we demonstrate that upon transduction these vectors now produce a majority of shortened subgenomic species and as a consequence have a reduced tendency for subsequent mobilization from transduced cells. In addition, we demonstrate that the use of this internal signal leads to enhanced expression from such vectors and that this is achieved without any loss in titer. Therefore, split polyadenylation signals confer enhanced performance and improved safety upon retroviral expression vectors into which they are inserted. Such split signals may prove useful for the future optimization of retroviral vectors in gene therapy.